Colección de documentos del escritor y editor Gregorio Martínez Sierra: recuperación y tratamiento - Sánchez Vigil, Juan Miguel (Revista General de Información y Documentación, 2009)
Study of a documentary corpus on the professional activity of the writer, journalist and publisher Gregorio Martínez Sierra in relation with the theatre and his collaborations in the Latin American press, particularly in the Mexican newspapers El Universal and Diario de Yucatán. All the work involved in the recovery, evaluation and processing of the documents is covered. A detailed inventory and an alphabetical index for the recovery of the information are the end results.
Keywords: Gregorio Martínez Sierra; Theatre; Theatrical documentation; Actors; Actresses; Press; Latin American press; Journalistic documentation; El Universal and Diario de Yucatán